The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1353/aad.2012.1329
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in Rubella Deaf Children: A Longitudinal Study

Abstract: Within a longitudinal study of children with congenital rubella, 85 Deaf Only adolescents, 85 Deaf Multihandicapped, and 34 Normal controls were studied with respect to impulsivity. The majority of the deaf group had severe or profound hearing loss. Prevalence of impulsivity and self abuse clearly differentiated Deaf Only from Deaf Multihandicapped. In adolescence, one-fifth of the Deaf Only and three-fifths of the Deaf Multihandicapped showed impulsivity; only Deaf Multihandicapped were self abusive. For both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The diagnosis of ADHD is often confounded by factors such as a perceived increase in impulsivity in deaf children (Harris, 1978 ;O'Brien, 1987), particularly in children with deafness due to congenital rubella with additional impairments (Chess & Fernandez, 1980). The deaf child's reliance on visual cues in the classroom as well as at play can add to these diagnostic difficulties.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…The diagnosis of ADHD is often confounded by factors such as a perceived increase in impulsivity in deaf children (Harris, 1978 ;O'Brien, 1987), particularly in children with deafness due to congenital rubella with additional impairments (Chess & Fernandez, 1980). The deaf child's reliance on visual cues in the classroom as well as at play can add to these diagnostic difficulties.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%
“…In a study of teacher-identified problem behaviors in deaf children, Reivich and Rothrock (1972) suggested that impulsivity and a lack of inhibitory control accounted for a significant amount of the problem behaviors reported. Chess and Fernandez (1980) reported elevated levels of impulsive behavior in deaf children manifest as aggressive acts such as kicking, hitting, and biting. Theirs was a study of deaf children whose mothers had Rubella during gestation, and the aggressive behaviors were more prevalent in those with multiple disabilities, than in the healthy children with deafness alone.…”
Section: Introductionmentioning
confidence: 99%
“…They include, but are not limited to, patent ductus arteriosis, pulmonic stenosis, aortic stenosis, atrial septal defect and ventricular defect. A total of 32.5% of the cases had cardiac lesions of different types (7). O'Donnell gathered information on 88 individuals with CRS found that 32% had a heart condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focused on the CRS triads: hearing impairments, cataracts and congenital heart disease (7). Later, the distinguishing CRS features expanded to include low birth weight and delayed neonatal growth, thrombocytopenic purpura, transient bone lesions, anemia, hepatitis, microcephaly, psychomotor retardation and other disorders(5, 8, 9).…”
Section: Introductionmentioning
confidence: 99%